2021
DOI: 10.36663/tatefl.v2i1.179
|View full text |Cite
|
Sign up to set email alerts
|

Developing an Android-Based English Reading Material for the Eighth Grade Students in Mtsn Karangasem

Abstract: This study intended to develop an android-based application for English reading material learning for the eighth-grade students in MTsN Karangasem. This study used the design and development design model proposed by Richey & Klein (2014) which consisted of three major steps namely; 1) Design, 2) Development, 3) Evaluation. The subjects of this study were the eighth grade students of MTsN Karangasem, the English teacher in MTsN Karangasem, and integrated technology experts. The instruments used in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The next research from (Abdalqadir, 2017) who had developed a mobile application to teach English, and the result was that the application should make it easy to learn English as a second language. Rahmanita et al (2021) have also suggested that developing English learning mobile android-based applications helps students interested in learning English language quickly and efficiently because of its coupled interactive features, which have been shown to be very effective in mobile learning activities. Hence, this recent research has developed appropriate mobile learning applications as media in reading comprehension for tenth graders based on the ADDIE model of development (Drljača et al, 2017).…”
Section: A Introductionmentioning
confidence: 99%
“…The next research from (Abdalqadir, 2017) who had developed a mobile application to teach English, and the result was that the application should make it easy to learn English as a second language. Rahmanita et al (2021) have also suggested that developing English learning mobile android-based applications helps students interested in learning English language quickly and efficiently because of its coupled interactive features, which have been shown to be very effective in mobile learning activities. Hence, this recent research has developed appropriate mobile learning applications as media in reading comprehension for tenth graders based on the ADDIE model of development (Drljača et al, 2017).…”
Section: A Introductionmentioning
confidence: 99%